A characterization of the Rogers q-hermite polynomials - Waleed A. Al-Salam (International Journal of Mathematics and Mathematical Sciences)
In this paper we characterize the Rogers q-Hermite polynomials as the only orthogonal polynomial set which is also 𝒟q-Appell where 𝒟q is the Askey-Wilson finite difference operator.